Choroidal and retinal blood flow changes in degenerative myopia - Akyol, N; Kukner, AS; Ozdemir, T; Esmerligil, S (Canadian Ophthal Soc, 1996)
Objective: To determine changes in choroidal and retinal blood flow in myopic Design: Case-control study. Setting: Ophthalmology department of a university-affiliated hospital in Elazig, Turkey. Subjects: Twenty-one consecutive patients (40 eyes) with degenerative myopia and 20 age-matched healthy emmetropic volunteers (38 eyes). Both groups were free of any systemic disease, such as diabetes mellitus or hypertension, that can affect micro- or macrocirculation. Outcome measures: Posterior ciliary artery and central retinal artery peak systolic, peak diastolic and mean blood flow velocity (measured with colour Doppler ultrasonography), pulsatility index and resistance index. Results: The posterior ciliary artery mean peak systolic (12.34 vs. 16.90 cm/s) and peak diastolic (3.12 vs. 5.10 cm/s) blood flow velocity values were significantly lower in the study group than in the control group (p < 0.001). There was a significant difference in the posterior ciliary artery resistance index between the two groups (0.74 vs. 0.69) (p < 0.05). The central retinal artery mean peak systolic (6.64 vs. 9.72 cm/s) and peak diastolic (2.01 vs. 3.07 cm/s) blood flow velocity values were also significantly lower in the study group than in the control group (p < 0.001). Conclusion: Choroidal and retinal blood now was decreased in degenerative myopia The reduced choroidal blood now may be partly due to increased vascular resistance, Decreased retinal blood now is probably an adaptive change.
Keywords: myopia; ocular blood flow; colour Doppler imaging